If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4z = 5z + -18 Reorder the terms: 4z = -18 + 5z Solving 4z = -18 + 5z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-5z' to each side of the equation. 4z + -5z = -18 + 5z + -5z Combine like terms: 4z + -5z = -1z -1z = -18 + 5z + -5z Combine like terms: 5z + -5z = 0 -1z = -18 + 0 -1z = -18 Divide each side by '-1'. z = 18 Simplifying z = 18
| 2a+3b=83 | | 2p^3q^2+p^2q+pq= | | 8(v+2)-4v=2(2v+1)-11 | | -3m=j-18 | | 13s-19s=18 | | 3y^2+8=36 | | 9y+9=8y-8 | | -5x+34x+7= | | 67n=-22 | | 2p^3+p^2q+pq= | | -5p+2+6p=9 | | -694=.83r | | 2x^2+27x-5.1=0 | | -.125x=-4 | | .1b=-108 | | 3(4z-1)-5(z+1)=3(z+1) | | 3y-12=7 | | .05=.6m | | 3x^2+4+1= | | -.75k=.67 | | -13x^3+20x-7=0 | | 18=-.5t | | -4d+2(4+9)=-14 | | 0.083n=12 | | 9m-13=-22+8m | | 36y=108 | | x^3-x^2-1120=0 | | x=-3y^2-12y | | 3(x-4)-2(x+2)-13=-20 | | (3x-12)-2x+-2-13=-20 | | 3x-12-2x+4-13=20 | | 24x^3-21x^2= |